AN INFORMATION SYSTEM SUCCESS MODEL FOR CLOUD COMPUTING IN INFORMATION TECHNOLOGY PROJECT - Zulfan Zulfan (UIN Ar-Raniry, 2018)
Cloud computing is becoming an attractive technology due to its dynamic scalability and effective usage of the resources, it can be utilized under circumstances where the availability of resources is limited. The main aim of this study is to develop an IS successful model for cloud computing in IT project environment. There were 38 respondents participated in this study. Data were collected by surveys and analyzed by SPSS. The findings of the study revealed that the system under study was quite successful on use of cloud computing in IT project assignment and very useful. In addition to all hypotheses in this study were interrelated.